2019
DOI: 10.1111/jcmm.14691
|View full text |Cite
|
Sign up to set email alerts
|

Dl‐3n‐butylphthalide improves traumatic brain injury recovery via inhibiting autophagy‐induced blood‐brain barrier disruption and cell apoptosis

Abstract: Blood-brain barrier (BBB) disruption and neuronal apoptosis are important pathophysiological processes after traumatic brain injury (TBI). In clinical stroke, Dl-3nbutylphthalide (Dl-NBP) has a neuroprotective effect with anti-inflammatory, anti-oxidative, anti-apoptotic and mitochondrion-protective functions. However, the effect and molecular mechanism of Dl-NBP for TBI need to be further investigated.Here, we had used an animal model of TBI and SH-SY5Y/human brain microvascular endothelial cells to explore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Growing evidence has indicated that overactivated autophagy under pathological conditions can trigger cell death and BBB damage; for example, following a stroke in diabetic mice, the expression of autophagy-related proteins was increased, while that of the TJ protein occludin was decreased, and 3-MA reversed these effects ( 70 , 71 ). Wu et al reported that Dl-3n-butylphthalide can exert neuroprotective effects by inhibiting autophagy and blocking TJ protein loss ( 72 ). Our previous study also revealed that hyperglycemia increased LC3 II/I expression following cerebral I/R injury ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has indicated that overactivated autophagy under pathological conditions can trigger cell death and BBB damage; for example, following a stroke in diabetic mice, the expression of autophagy-related proteins was increased, while that of the TJ protein occludin was decreased, and 3-MA reversed these effects ( 70 , 71 ). Wu et al reported that Dl-3n-butylphthalide can exert neuroprotective effects by inhibiting autophagy and blocking TJ protein loss ( 72 ). Our previous study also revealed that hyperglycemia increased LC3 II/I expression following cerebral I/R injury ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pericyte apoptosis also increases BBB permeability, which, in turn, diminishes the stability of the brain microenvironment ( Armulik et al, 2010 ; Liu S. et al, 2012 ). The biochemical compounds targeting endothelial cell and pericyte apoptosis exert promising effects on functional recovery after central nervous system injury ( Hu et al, 2017 ; Song et al, 2018 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two days after the initial TBI, in the aged animal group, we were able to detect a decrease in the apparent lesion area which could show a delayed response in older animals compared with young ones, as already reported by other groups (Brickler, Morton, Hazy, & Theus, 2018; Kumar et al, 2013; Marker et al, 2010). Due to the fact that our OCT setups cannot discriminate individual cells within the newly form scar, our findings suggest that, at least for the acute phase of the TBI, this technique evaluates water content and not reflected patterns due to cell density, as in this period water metabolism varies faster that cellular migration or proliferation (Wu et al, 2020). When measuring the apparent OCT lesion, no difference was found between young and old animal 48 hr after the initial TBI.…”
Section: Discussionmentioning
confidence: 99%